Methodology of application of shamanic practice in Malay community - Abdullah, Shazlin; Noor Muhammad, Salmah Jan (Human Resource Management Academic Research Society, 2020)
Shamanism is a way of thinking with an exclusive value. The dependency of Malay society to shamans has been a symbol of their belief. The aim of this research is to identify and analyse the materials used and the methodology of application in shamanic practice by the Malay society. This research employed a qualitative methodology including library research and respondents interview. This research also solely focuses on the methodology of application in shamanic rituals among Malay society at Pantai Cahaya Bulan, Kelantan. Social Anthropology Theory explored by Koentjaraningrat has been used as a reference in this research analysis. The results showed that methodology of application of the practice involved having a flower and lime water bath ritual which is closely related to natural ingredients. Therefore, this research will provide society with knowledge about shamanic rituals that are still heavily practiced among Malay society until today.